Tautiniai santykiai Lietuvoje 1988-1992 metais - Biveinis, Petras; Kasperavičius, Algis Povilas (Lietuvos istorijos studijos, 2007)
During centuries Lithuania has saved a rich experience of a peaceful and easy disposition of different nations, which experienced a stiff task during the period of Lithuania's sovereignty restoration and consolidation. The article analyses the relationship of national majorities Lithuanians, and national minorities - Russians, Poles, Jews, partly Belorussians and other. Russians and Poles are the biggest national minorities in Lithuania. Jews demonstrated an absolutely beneficial attitude to the Lithuanian statehood as distinct from the part of Russians and Poles.The period is short, but it reflects the topic of national relationship in Lithuania. The basic factor, which was endangering the peaceful and easy disposition of nations in 1988, was the inflammatory activity of communistic structures, post-Soviet organizations. Pro-imperial forces were operating under a principle "divide-and-rule".The article shows that the majority of other nations (Russians, Poles, Belorussians) were not against Lithuanians' national movement, striving for independence, however the part of them became the hostages of pro-communistic organizations. The characters of communistic nomenclature managed to relate the national interest of Poles with the demand of territorial national autonomy. Whereas Jews approved of Lithuanians' national objectives.However, the national relationship in Lithuania was complicated by some mistakes of Movement and national institutions - the pronouncement of Lithuanian language as national without ascertaining the status of other languages, ensuing unrealistic demand in companies, agencies and organizations, which were administering its record-keeping in Russian language, to convert to Lithuanian language within two years. The relationship with Lithuanian Poles was complicated by the emotional treatment of historical past, the temerarious point, that they are Lithuanians with Polish manners; the relationship with Lithuanian Poles was complicated by a quite frequent harassment concerning the events of Soviet times, which aroused psychological experiences. The mythologized human consciousnesses, the immature political culture (objective justification of phenomenon) were increasing the international tension.Tragic January events increased the foreign-borns' approval to the objectives of Lithuanians.In the pending period of national relationship the perception of problems was concurrent from general political and social-economical process. The complex attitude to the period of post-communistic transformations helps to fathom out the topicalities. After the failure of August putsch, the development of national relationship was largely determined by reforms, social-economical alterations, also the artificial increase of tension in society; relationship between Lithuanians and Jews, manifestation of anti-Semitism. Integration of Lithuanian Republic into the community of global nations, the admission of Constitution and other law certificates presumed the stabilization of national relationship.